Fabrication and performance evaluation of aminopropyl triethoxysilane-dopamine-MoS2 incorporated SBS modified asphalt. (30th December 2020) - Wei, Yunhao; Hu, Chengwei; Muhammad, Yaseen; Chen, Lishan; Zhou, Dali; Wang, Shanshan; Li, Jing; Chen, Qihang
Graphical abstract: Highlights: MoS2 was modified by Aminopropyl triethoxysilane-Dopamine via facile approach. APs-DA-MoS2 /SBS modified asphalt showed better Viscoelastic properties. APs-DA-MoS2 /SBS modified asphalt realized enhanced rutting resistance, fatigue performance and thermal stability. APs-DA-MoS2 modified asphalt showed well developed network structure. Abstract: In this study, a green and simple method was developed to deposit aminopropyl triethoxysilane-Dopamine (APs-DA) hybrid coating on the surface of MoS2 under mild reaction conditions using non-toxic reagents. The resulting composite (APs-DA-MoS2 ) was in turn used as a modifier to conventional styrene–butadienestyrene (SBS) modified asphalt. The deposition of APs-DA over MoS2 and spherical morphology of the composite was confirmed by Fourier transform infra-red (FT-IR) spectroscopy, X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Thermogravimetric analysis (TGA) showed higher thermal stability (increased initial decomposition temperature by 28 °C) of APs-DA-MoS2 incorporated asphalt as compared to the pristine SBS modified asphalt. Fluorescence microscopy (FM) confirmed the development of a proper network structure in the APs-DA-MoS2 modified asphalt which contributed towards its enhanced mechanical, viscoelastic and thermal stability properties, resistance against rutting and fatigue performance as confirmed by dynamic shear rheological (DSR), multi stress creep and recovery (MSCR), time sweep and rotational viscosity (RV) tests. The elastic modulus (G') (46 °C, 10 Hz) of SBS modified asphalt was increased by 51.09% upon the incorporation of 0.08% APs-DA-MoS2 . Attributed to the facile and environmentally benign synthesis approach, enhanced mechanical properties, thermal stability, resistance against rutting and fatigue performance, this study provides useful reference for the fabrication of APs-DA-MoS2 modified asphalt for practical applications in highway and construction industry.